PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PT INDOSAT TBK - Jurnal Ilmiah Manajemen UPB (Universitas Putera Batam, 2017)
This study tried to see Does the company's profitability may be affected by liquidity and solvabilits in PT Indosat period 2011-2015 either partially or simultaneously using multiple linear regression analysis as well as quantitative data in the form of financial statements of PT Indosat. From the test results we got the result that the liquidity and solvency together can significantly influence the profitability of the company, but in partial liquidity but no significant effect on the solvency significantly affect the profitability.